2011
DOI: 10.1039/c1cy00207d
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in “sacrificial” solvents

Abstract: The involvement of organic solvents in redox reactions and their influence on the efficiency and ''greenness'' of the desired chemical transformation are critically reviewed. Some representative examples are presented on the co-oxidation and co-reduction of widely used solvents (alcohols, ethers, nitriles, amides, sulfoxides, hydrocarbons, dense CO 2 ), and on the impact of these frequently hidden reactions. The transformation of the solvent may be limited to its unintended consumption leading to an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 221 publications
(246 reference statements)
0
36
0
Order By: Relevance
“…An additional strong O-C=O peak (1569 cm −1 ), corresponding to conjugated γbutyrolactone, was observed for the AgNS-AgFLs. The 2-hydroxy tetrahydrofuran, formed in the reaction medium, generated conjugated γ-butyrolactone as a byproduct upon further oxidation 35,36 . Additional peaks related with SR (Si(CH 3 ) 2 stretching, Si-O-Si stretching, Si-CH 3 stretching, and CH bending) were observed for the AgNS-AgFL-SR nanocomposite 37 .…”
Section: Resultsmentioning
confidence: 99%
“…An additional strong O-C=O peak (1569 cm −1 ), corresponding to conjugated γbutyrolactone, was observed for the AgNS-AgFLs. The 2-hydroxy tetrahydrofuran, formed in the reaction medium, generated conjugated γ-butyrolactone as a byproduct upon further oxidation 35,36 . Additional peaks related with SR (Si(CH 3 ) 2 stretching, Si-O-Si stretching, Si-CH 3 stretching, and CH bending) were observed for the AgNS-AgFL-SR nanocomposite 37 .…”
Section: Resultsmentioning
confidence: 99%
“…By using propionitrile as a solvent, a drastic increase in reactivity was observed (making the determination of rate constants for 4 +O 2 impossible), with no change in the overall trend (see Section 1.3.1.2 in the Supporting Information). Notably, an active participation of the solvents in the reaction mechanism, as an alternative conceivable explanation,—could be ruled out (Section 2, Supporting Information). When the experiments were repeated with 2,6‐dimethylphenol as the substrate (BDE 84.50 kcal mol −1 ), which has a far stronger O−H bond, the reaction slowed down to such an extent that an extra set of absorption bands could be observed by UV/Vis spectroscopy (Li + 561, 594; Na + 507, 583; K + 509, 574 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The report of Yuan et al., [87] however, remains a significant breakthrough, for although H 2 O 2 had previously been identified as a suitable oxidative species for methane oxidation, its use was typically reported in chemically reactive organic solvents 88. 90 Care must be taken whilst examining these previous results, therefore, as it has previously been reported that this can lead to both the formation of more reactive oxygen donors (such as peroxyacetimidic acid or peroxycarboximidic acid) or lead directly to C 1 ‐oxygenated species via co‐oxidation or degradation of the organic solvent 91. This is hugely undesirable on a process level, as it results in the production of non‐methane‐derived oxygenated species and the degradation of the desired solvent.…”
Section: Partial Oxidation Of Methanementioning
confidence: 99%